Food Market in Constanta County: ANSVSA Monitoring Actions in 2022 Summer Season - Iuliana CONDULEȚ; Silvius STANCIU (Communications of International Proceedings, 2022)
This paper presents an analysis of the results of the monitoring and control actions of the food products sold as goods or services on the Romanian market during the 2022 summer season. The National Sanitary Veterinary and Food Safety Authority regularly carries out actions concerning the economic operators in the sector, in order to increase the level of food safety and reduce the level of the risk factors to the population's health. The study focused on the controls carried out in Constanța County, the coastal Black Sea area, which is characterized by a high influx of tourists during the summer season. The research revealed the fact that there are economic operators in the food sector who, even in the year 2022, do not comply with certain national legislative regulations on food products’ safety and hygiene and consumer health’s protection. The controls of the 2022 Summer Season Command, carried out between June 27 and August 28, 2022, achieved their main declared objective, i.e., to achieve zero food poisoning at the level of the consumers, but they revealed that there is still a lack of interest and awareness on the part of the economic operators evaluated. The results of the research show that it was necessary to impose penalties and seizures of non-compliant food products, in correlation with the volume of the thematic controls carried out and with the number of registered sanitary veterinary and food safety units assessed. The deviations from food products’ quality detected as a result of the actions carried out by the relevant control bodies on the food market in Constanța have not been sporadic, being proportional to the frequency and number of controls. The legislation in Romania is consistent for any field of activity in the food sector, each economic operator being responsible for complying with these regulations, in order to protect the health of the final consumer. The analysis carried out is part of some doctoral research, whose main objective is food quality and the increase of the level of food products’ safety on the Romanian market.
Keywords: Non-compliance; Measures; ANSVSA; 2022 Season